2018
DOI: 10.1213/ane.0000000000002329
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Considerations for Physiological Closed-Loop Controlled Medical Devices Used for Automated Critical Care: Food and Drug Administration Workshop Discussion Topics

Abstract: Part of the mission of the Center for Devices and Radiological Health (CDRH) at the US Food and Drug Administration is to facilitate medical device innovation. Therefore, CDRH plays an important role in helping its stakeholders such as manufacturers, health care professionals, patients, patient advocates, academia, and other government agencies navigate the regulatory landscape for medical devices. This is particularly important for innovative physiological closed-loop controlled (PCLC) devices used in critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…We have implemented safeguards for automatically correcting pump inlet starvation (suckdown) and for preventing conditions of inadequate CO 2 removal in the setting of adequate oxygenation. The AR‐ECMO system would be considered a physiologic closed loop‐controlled medical device as defined by the United States Food and Drug Administration, and approval of such a device requires satisfactory demonstration of system performance and stability. Although seeking approval of such a device poses a substantial challenge, we believe that automatic adaptation is a necessary feature of an out‐of‐hospital artificial lung, and we aim to provide patients with such a device.…”
Section: Discussionmentioning
confidence: 94%
“…We have implemented safeguards for automatically correcting pump inlet starvation (suckdown) and for preventing conditions of inadequate CO 2 removal in the setting of adequate oxygenation. The AR‐ECMO system would be considered a physiologic closed loop‐controlled medical device as defined by the United States Food and Drug Administration, and approval of such a device requires satisfactory demonstration of system performance and stability. Although seeking approval of such a device poses a substantial challenge, we believe that automatic adaptation is a necessary feature of an out‐of‐hospital artificial lung, and we aim to provide patients with such a device.…”
Section: Discussionmentioning
confidence: 94%
“…Clearly, the development of mathematical models for control design [347] and evaluation remain important areas of research in physiological closed-loop control. Further, while we have mentioned that some methods of control do not require an explicit mathematical model, these methods may be difficult to evaluate in a computational setting, and considering the risks involved with physiological systems the immediate future of such methods in PCLC -especially with regard to regulatory approval -is unclear [9]. Of course, the effectiveness of model-based control is itself subject to the appropriateness of the model(s) used for controller design [347], and a recent review [348] has shown that many published methods fall short of completely demonstrating their suitability to the proposed use (e.g., controller design, closed-loop performance evaluation, hardware-in-the-loop testing) in PCLC devices.…”
Section: Discussion and Future Of Physiological Closed-loop Controlmentioning
confidence: 99%
“…Recognizing the generality of this concept, many agencies and organizations are in the process of developing more rigorous guidelines for commercial PCLCs that will help to establish the scope of this up-and-coming class of devices. As noted in a recent paper from researchers at the Center for Devices and Radiological Health (CDRH) at the US Food and Drug Administration (FDA), the CDRH maintains a working definition of PCLC medical devices (or PCLC devices) as, "a medical device that incorporates physiological sensor(s) for automatic manipulation of a physiological variable through actuation of therapy that is conventionally made by a clinician" [9]. This definition -demonstrated in Fig. Ib -recognizes the role of automation in PCLC while allowing a great deal of flexibility in the disorder being treated, the types of sensors and therapies used (many are certainly yet to be discovered), and the extent to which the PCLC operates independent of clinician intervention -known as the level of automation (LOA) [9].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the patient is the focus of the control loop and a physiological measurement is fed back to the controller. The PCLC has recently been taken up by regulatory bodies, with an international standard developed specifically for it, namely the IEC 60601-1-10 [2] and a public workshop held by the Food and Drug Administration in 2015 with subsequent publication by Parvinian and colleagues in 2018 [3].…”
Section: Introductionmentioning
confidence: 99%